2007
DOI: 10.1021/tx700132x
|View full text |Cite
|
Sign up to set email alerts
|

NADPH-Dependent Covalent Binding of [3H]Paroxetine to Human Liver Microsomes and S-9 Fractions: Identification of an Electrophilic Quinone Metabolite of Paroxetine

Abstract: The primary pathway of clearance of the methylenedioxyphenyl-containing compound and selective serotonin reuptake inhibitor paroxetine in humans involves P450 2D6-mediated demethylenation to a catechol intermediate. The process of demethylenation also results in the mechanism-based inactivation of the P450 isozyme. While the link between P450 2D6 inactivation and pharmacokinetic interactions of paroxetine with P450 2D6 substrates has been firmly established, there is a disconnect in terms of paroxetine's excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 36 publications
3
69
0
Order By: Relevance
“…This finding is supported by results from van der Lee et al (2007), who stated that combining phenytoin (a CYP3A4 inducer) with paroxetine decreased paroxetine levels. These inferences are also supported by the finding that paroxetine is a weak mechanismbased inhibitor of CYP3A , especially given that the reactive species most likely does not leave the active site before inactivation (Zhao et al, 2007), also suggesting involvement of CYP3A4 in paroxetine metabolism.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…This finding is supported by results from van der Lee et al (2007), who stated that combining phenytoin (a CYP3A4 inducer) with paroxetine decreased paroxetine levels. These inferences are also supported by the finding that paroxetine is a weak mechanismbased inhibitor of CYP3A , especially given that the reactive species most likely does not leave the active site before inactivation (Zhao et al, 2007), also suggesting involvement of CYP3A4 in paroxetine metabolism.…”
mentioning
confidence: 69%
“…The mechanism-based inhibition (MBI) is most likely caused by an irreversible binding of a paroxetinereactive metabolite, one that does not leave the active site, to the heme complex in the P450 enzyme (Bertelsen et al, 2003;Zhao et al, 2007). The MBI kinetic constants (K inact and K I ) have been determined for CYP2D6 and CYP3A (Bertelsen et al, 2003;Obach et al, 2007).…”
mentioning
confidence: 99%
“…Inclusion of NADPH and GSH in liver microsomal incubations led to an even more rapid decline of BETP and the quantitative conversion to GSH adduct M1, which is indicative of a detoxifying metabolic pathway that competes with protein covalent binding. The propensity of GSH to reduce microsomal covalent binding has been noted with several drugs that are bioactivated to electrophilic species (Zhao et al, 2007;Obach et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This antidepressant is an important representative of an emerging group of pharmacologically active 4-aryl piperidines (Scheme 2). Recent studies have shown that paroxetine and its metabolites [17][18][19][20] have the potential to accumulate in waste waters, 3, 21 but also in the tissue of fish 22 as a result of discharges of this antidepressant into surface waters from municipal wastewater treatment plants. Therefore, interest in conducting the environmental risk assessment of paroxetine continues unabated.…”
Section: Scheme 1 Different Rearrangement Reactions In N-chloraminesmentioning
confidence: 99%